2017
DOI: 10.1039/c7cp07203a
|View full text |Cite
|
Sign up to set email alerts
|

The cohesive energy of superheavy element copernicium determined from accurate relativistic coupled-cluster theory

Abstract: The cohesive energy of bulk copernicium is accurately determined using the incremental method within a relativistic coupled-cluster approach. For the lowest energy structure of hexagonal close-packed (hcp) symmetry, we obtain a cohesive energy of -36.3 kJ mol (inclusion of uncertainties leads to a lower bound of -39.6 kJ mol), in excellent agreement with the experimentally estimated sublimation enthalpy of -38 kJ mol [R. Eichler et al., Angew. Chem. Int. Ed., 2008, 47, 3262]. At the coupled-cluster singles, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 66 publications
4
16
0
10
Order By: Relevance
“…Recently, the solid phases of Cn have been explored by means of highly accurate method‐of‐increment relativistic coupled cluster (MOI‐CC) calculations . In excellent agreement with the experimental estimate, these calculations provided a cohesive energy of −0.38±0.03 eV, and moreover revealed that hcp is the most stable phase and quasi‐degenerate with fcc and bcc .…”
Section: Figurementioning
confidence: 75%
See 2 more Smart Citations
“…Recently, the solid phases of Cn have been explored by means of highly accurate method‐of‐increment relativistic coupled cluster (MOI‐CC) calculations . In excellent agreement with the experimental estimate, these calculations provided a cohesive energy of −0.38±0.03 eV, and moreover revealed that hcp is the most stable phase and quasi‐degenerate with fcc and bcc .…”
Section: Figurementioning
confidence: 75%
“… Melting and boiling points (in K) as well as cohesive energies (lattice energy of the most stable phase in eV/atom) of the Group 12 elements zinc (Zn), cadmium (Cd), mercury (Hg), and copernicium (Cn) . The yellow area indicates ambient conditions, for which we assume a temperature range of 288.15–298.15 K (15–25 °C) based on the standard ambient temperature and pressure (SAPT of IUPAC: 25 °C), normal temperature and pressure (NTP of NIST, 15 °C), and international standard atmosphere (ISA, 20 °C).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…shown in the figure makes Cn chemically more inert compared to the lighter congener Hg (Eichler et al, 2008;Gaston et al, 2007;Pitzer, 1975;Steenbergen et al, 2017a), where relativistic effects are known to be large; they are responsible for Hg being the only elemental liquid metal at room temperature (Calvo et al, 2013;Steenbergen et al, 2017b).…”
Section: Chemistry and Relativistic Effectsmentioning
confidence: 99%
“…[16],w ew ill focus here on the evolution of DE, O g ,a nd E g with increasing atomic number.B ys imple extrapolation based on Figure 2, one would anticipate aneardegeneracyofthe three at about 7eVfor Rn, and values just above 4eVf or Og, placing the latter at the borderline between insulators and semiconductors.H owever,s uch as imple extrapolation disregards that the close resemblance between atomic and bulk properties may break in the heavier noble gases which are larger,m ore polarizable and thus interact more strongly.This is reflected in the cohesive energy (E coh ,b inding energy of the solid per atom, red line in Figure 2), which increases continuously to 0.23 eV for Rn, and jumps to 0.45 eV for Og. [19,20] Hence,O gi sb yf ar the least noble of the noble gases,l ess noble even than superheavy copernicium (Cn, E coh = 0.38 eV) [22][23][24] and thus presumably also as olid at ambient conditions.A ccordingly,e xcitons in solid Og and perhaps also Rn may exhibit adelocalization and stabilization compared to the respective excited states of the atoms,w hich could cause O g and E g to fall well below DE, breaking with the periodic trends and rendering Og as emiconductor.…”
mentioning
confidence: 99%